Geological control of mineral deposits in Nepal (Journal of Nepal Geological Society, 2019)
Systematic information and in-depth knowledge of geological controls, mode of occurrences, distribution patterns and mineral association are very essential for exploring the new deposits and development of mineral resources of the country in general. In present study, an attempt has been made to clarify the geological controls of economic and sub-economic mineral deposits of Nepal. Investigation has shown that mineral deposits in Nepal Himalaya are controlled by particular geological conditions and tectonics. Till the date, economic potential of 63 mineral commodities from Nepal have been established by Department of Mines and Geology. Several economic to sub economic deposits of the country are explored and some are under mining process. Analysis of geological controls of above mentioned economic and sub-economic mineral deposits shows that they are either syngenetically or epigenetically confined to particular stratigraphic and tectonic units. These deposits are related in time and space to certain events of crustal movement representing different metallogenic epochs.